2012
DOI: 10.1186/1742-6405-9-9
|View full text |Cite
|
Sign up to set email alerts
|

Sexual behavior of HIV-positive adults not accessing HIV treatment in Mombasa, Kenya: Defining their prevention needs

Abstract: BackgroundHIV spread continues at high rates from infected persons to their sexual partners. In 2009, an estimated 2.6 million new infections occurred globally. People living with HIV (PLHIV) receiving treatment are in contact with health workers and therefore exposed to prevention messages. By contrast, PLHIV not receiving ART often fall outside the ambit of prevention programs. There is little information on their sexual risk behaviors. This study in Mombasa Kenya therefore explored sexual behaviors of PLHIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 48 publications
0
14
1
Order By: Relevance
“…More than 77% of the people living with HIV were sexually active in the past 12 months preceding the study. This is a high proportion compared to previous studies conducted in Uganda [12], [23] and elsewhere within the East African region [15], [16]. The increase in sexual activity among PLHIV could be attributed to improved quality of life because of antiretroviral therapy, opportunistic infection prophylaxis and other health care packages.…”
Section: Discussionmentioning
confidence: 76%
“…More than 77% of the people living with HIV were sexually active in the past 12 months preceding the study. This is a high proportion compared to previous studies conducted in Uganda [12], [23] and elsewhere within the East African region [15], [16]. The increase in sexual activity among PLHIV could be attributed to improved quality of life because of antiretroviral therapy, opportunistic infection prophylaxis and other health care packages.…”
Section: Discussionmentioning
confidence: 76%
“…For instance, studies show that condom use fatigue, HIV transmission myths, lack of HIV knowledge, and a desire to have children may lead to PLWHA ignoring the risks of unprotected sex. 1,14,15 Conversely, self-efficacy regarding safe sex, and motivation to protect partners as well as themselves against re-infection with new HIV strain or other STIs may lead to safe sex practices among HIV-positive individuals. 15 Expanded access to anti-retroviral drugs (ARV) has enabled people with HIV to live longer and healthier lives.…”
Section: Introductionmentioning
confidence: 99%
“…1,14,15 Conversely, self-efficacy regarding safe sex, and motivation to protect partners as well as themselves against re-infection with new HIV strain or other STIs may lead to safe sex practices among HIV-positive individuals. 15 Expanded access to anti-retroviral drugs (ARV) has enabled people with HIV to live longer and healthier lives. Consequently, the increasing number of sexual transmissions of HIV may result from those who know their HIV-seropositive status but engage in sexual risk behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have either examined case management in conjunction with other services, such as counseling and prevention interventions, or has examined the effects of case management only on HIV risk behaviors among specific populations, such as prisoners and PLWH outside of the United States (Gasiorowicz, 2005;Johnson, 2008;Johnson, 2010;Joseph, 2010;Ko, 2011;Luchters, 2008;Robles, 2004;Sarna, 2012;Schumann, 2007). These previous studies report conflicting results; some show reduced risk behaviors and others found no change in risk behaviors.…”
Section: Discussionmentioning
confidence: 99%